Margins of learning spaces by bookmaking at university curricular units - Serra de Magalhães Rocha, Ana Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article intends to unpack how art education motivates students for a creative educational practice in immersive learning, following the author’s research using books to explore The Book Experience as a Place of Epistemological Reflection in Art Education. Questions as to how book making can be understood as a tool for teaching and learning, as a mediator and as a collaborative piece of producing knowledge, were raised during the process of making collective books, along with reflection on author’s articles. Feedbacks reveal a firm evidence of learning through studio practice based pedagogies as spaces of learning.